2017
DOI: 10.1186/s13722-017-0096-7
|View full text |Cite
|
Sign up to set email alerts
|

Testing the implementation and sustainment facilitation (ISF) strategy as an effective adjunct to the Addiction Technology Transfer Center (ATTC) strategy: study protocol for a cluster randomized trial

Abstract: BackgroundImproving the extent to which evidence-based practices (EBPs)—treatments that have been empirically shown to be efficacious or effective—are integrated within routine practice is a well-documented challenge across numerous areas of health. In 2014, the National Institute on Drug Abuse funded a type 2 effectiveness–implementation hybrid trial titled the substance abuse treatment to HIV Care (SAT2HIV) Project. Aim 1 of the SAT2HIV Project tests the effectiveness of a motivational interviewing-based bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 94 publications
(121 reference statements)
0
34
0
Order By: Relevance
“…As such, the ATTC strategy was identified as one of the most promising strategies for helping HIV-CBOs and their staff integrate the project's MIBI. However, given implementation and sustainment are acknowledged as multilevel processes (16,52), the staff-focused ATTC strategy was hypothesized to be a necessary, but not sufficient, strategy (14). Thus, building upon research that identified facilitation (i.e., process of interactive problem solving and support that occurs in a context of a recognized need for improvement and a supportive interpersonal relationship) as a promising strategy (53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63), we aimed to test the team-focused ISF strategy as an effective adjunct to the staff-focused ATTC strategy (14).…”
Section: Rationale For Testing the Isf Strategy As An Adjunct To The mentioning
confidence: 99%
See 4 more Smart Citations
“…As such, the ATTC strategy was identified as one of the most promising strategies for helping HIV-CBOs and their staff integrate the project's MIBI. However, given implementation and sustainment are acknowledged as multilevel processes (16,52), the staff-focused ATTC strategy was hypothesized to be a necessary, but not sufficient, strategy (14). Thus, building upon research that identified facilitation (i.e., process of interactive problem solving and support that occurs in a context of a recognized need for improvement and a supportive interpersonal relationship) as a promising strategy (53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63), we aimed to test the team-focused ISF strategy as an effective adjunct to the staff-focused ATTC strategy (14).…”
Section: Rationale For Testing the Isf Strategy As An Adjunct To The mentioning
confidence: 99%
“…As detailed by Garner et al (14) the ISF strategy is a multifaceted strategy with facilitation as the overarching discrete strategy, encompassing six additional discrete strategies (i.e., develop tools for quality improvement; organize implementation team meetings; identify and prepare champions; assess for readiness and identify barriers; conduct local consensus discussions; conduct cyclical small tests of change). Grounded in the theory of implementation effectiveness (20)(21)(22)(23), the ISF strategy seeks to improve implementation effectiveness (i.e., the consistency and quality of implementation of the clinical intervention) and intervention effectiveness (i.e., the clinical intervention's effectiveness in terms of improving client outcomes) via improving implementation climate (i.e., the extent to which implementation is expected, supported, and rewarded).…”
Section: Rationale For Testing the Isf Strategy As An Adjunct To The mentioning
confidence: 99%
See 3 more Smart Citations